Quantitative assessment of successive carbohydrate additions to the clustered O-glycosylation sites of IgA1 by glycosyltransferases. (9th December 2020) - Stewart, Tyler J; Takahashi, Kazuo; Xu, Nuo; Prakash, Amol; Brown, Rhubell; Raska, Milan; Renfrow, Matthew B; Novak, Jan
Abstract: Mucin-type O -glycosylation occurs on many proteins that transit the Golgi apparatus. These glycans impact structure and function of many proteins and have important roles in cellular biosynthetic processes, signaling and differentiation. Although recent technological advances have enhanced our ability to profile glycosylation of glycoproteins, limitations in the understanding of the biosynthesis of these glycan structures remain. Some of these limitations stem from the difficulty to track the biosynthetic process of mucin-type O -glycosylation, especially when glycans occur in dense clusters in repeat regions of proteins, such as the mucins or immunoglobulin A1 (IgA1). Here, we describe a series of nano-liquid chromatography (LC)–mass spectrometry (MS) analyses that demonstrate the range of glycosyltransferase enzymatic activities involved in the biosynthesis of clustered O -glycans on IgA1. By utilizing nano-LC–MS relative quantitation of in vitro reaction products, our results provide unique insights into the biosynthesis of clustered IgA1 O -glycans. We have developed a workflow to determine glycoform-specific apparent rates of a human UDP- N -acetylgalactosamine:polypeptide N -acetylgalactosaminyltrasnfersase (GalNAc-T EC 2.4.1.41) and demonstrated how pre-existing glycans affect subsequent activity of glycosyltransferases, such as core 1 galactosyltransferase and α2, 3- and α2, 6-specific sialyltransferases, in successive additions in the biosynthesis of clustered O -glycans. In the context of IgA1, these results have potential to provide insight into the molecular mechanisms implicated in the pathogenesis of IgA nephropathy, an autoimmune renal disease involving aberrant IgA1 O -glycosylation. In a broader sense, these methods and workflows are applicable to the studies of the concerted and competing functions of other glycosyltransferases that initiate and extend mucin-type core 1 clustered O -glycosylation.